MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA DI KELAS VIII B SMPN 2 TANTA PADA MATERI POKOK CAHAYA DAN ALAT OPTIK DENGAN MODEL PEMBELAJARAN STAD MENGGUNAKAN MEDIA AUDIO VISUAL - Hairani Hairani (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2013)
The research on “Light and Optics” using cooperative learning model types of STAD based audio visual media was conducted. This study aims to find out students 'improvement, motivation and student’s achievments, student’s and techer’s activities on STAD based audio visual media. This research used classaction-research design with 2 cycles. Subjects were students of eighth grade of Junior High School 2 Tanta. Totally, there were 19 students involved on this study. Data was collected by using achievement test, questionnaires, and observations. Subsequently, data were analyzed by using qualitative descriptive technique. The result showed that by using “STAD based audio visual media, student’s achievments on Light and Optics increased from 84,21%  on the first cycle to 89,47% on the second cycle. Student’s motivation and activities increased from good category  on the first cycle to very good category on the second cycle.Key words: Cooperative learning model types of STAD, audio visual media, light and optics.